2020
DOI: 10.1101/2020.06.24.20139188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 Antibody in Thai Community Hospitals

Abstract: Background: COVID-19 seroprevalence data has been scarce, especially in less developed countries with a relatively low infection rate. Methods: A locally developed rapid IgM/IgG test kit was used for screening hospital staff and patients who required procedural treatment or surgery in 52 hospitals in Thailand from April 8 to June 26, 2020. A total of 857 participants were tested--675 were hospital staff and 182 were pre-procedural patients. (Thai Clinical Trials Registry: TCTR20200426002) Results Ove… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 4 publications
(5 reference statements)
1
12
0
Order By: Relevance
“…Indeed, it was suggested that SARS-CoV-2 affected women less compared with men, due to different innate immunity, steroid hormones, and factors related to sex chromosomes ( 14 ). However, this female over male trend in asymptomatic carriers was not captured in other areas and countries, such as South Korea, Thailand, Iran, Spain, and California of USA ( 15 , 16 , 17 , 18 ). Whether this trend is observed only in Wuhan or can be observed in other parts of China or other countries too needs further investigation.…”
Section: Discussionmentioning
confidence: 90%
“…Indeed, it was suggested that SARS-CoV-2 affected women less compared with men, due to different innate immunity, steroid hormones, and factors related to sex chromosomes ( 14 ). However, this female over male trend in asymptomatic carriers was not captured in other areas and countries, such as South Korea, Thailand, Iran, Spain, and California of USA ( 15 , 16 , 17 , 18 ). Whether this trend is observed only in Wuhan or can be observed in other parts of China or other countries too needs further investigation.…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, intra-regional variations of seroprevalence were observed in healthcare workers, for example, seroprevalence among hospital staff in China range from 1.8% [ 5 ] to 17.1% [ 12 ] whereas seroprevalence of healthcare workers in Asia besides China and Southeast Asia ranged from 0.4% [ 13 ] to 9.1% [ 14 ]. In Southeast Asia, there were only two studies on the seroprevalence of COVID-19 in healthcare workers: one from Thailand reported a 3.7% seroprevalence [ 15 ], and one from Vietnam reported a zero seroprevalence [ 16 ]. Seroprevalences in healthcare personnel varied from 1.3% [ 17 ] to 45.3% [ 11 ] in Europe, from 0.8% [ 18 ] to 44.0% [ 19 ] in North America, from 0.9% [ 20 ] to 14.1% [ 21 ] in South America, and from zero [ 10 ] to 45.1% [ 22 ] in Africa whereas no seroprevalence studies were from Antarctica or Australia.…”
Section: Introductionmentioning
confidence: 99%
“…In China, for example, seroprevalence among hospital staff ranged from 1.8% (4) to 17.1% (9) whereas seroprevalence of healthcare workers in Asia besides China ranged from 3.3% (10) to 5.4% (11). In Southeast Asia, there was only a study from Thailand reported a 3.7% seroprevalence (12). Seroprevalences in healthcare personnel varied from 1.1% (13) to 45.3% in Europe (8) and from 2% (3) to 7.6% (14) in North America.…”
Section: Introductionmentioning
confidence: 99%